'A Still Ecstasy of Freedom and Enjoyment': Walking the City in Charlotte Brontë's Villette. (2nd October 2017) - Mathieson, Charlotte
Abstract: This article situates Charlotte Brontë's writing within the context of mid-nineteenth-century discourses of gender and travel, and posits that Brontë contributes to the discursive construct of the flâneuse through her writing about women walking the city in her letters from Belgium and in the novel Villette (1853). Through a critical framework drawing together literary historicism on women in the Victorian city and mobility theories of embodied and sensory movement, the analysis reveals how Brontë foregrounds the experience of the body in her writing of women walking, and uses this as a mode through which to explore gendered discourses of mobility, and especially women's urban walking. It argues that Brontë offers a new model of female urban spectatorship which privileges the body of the flâneuse as the prime site of knowing the city; this positively reconfigures the possibilities for autonomy and agency that urban walking affords, while at the same time making the body a site through which ambivalence about women's mobility is expressed. The article reveals Charlotte Brontë to be a writer actively engaged with discourses of mobility and modernity that have been overlooked in her work, and situates Brontë as a significant contributor to debates about women and the city. It advances literary histories of city walking by locating Villette as a key participant within the field, and contributes to Brontë studies by revealing new perspectives on the significance of women's travel in her works.